IEEE International Conference on Communications, 2005. ICC 2005. 2005 2005
DOI: 10.1109/icc.2005.1494499
|View full text |Cite
|
Sign up to set email alerts
|

Variable-size multipacket segments in buffered crossbar (CICQ) architectures

Abstract: Abstract-Buffered crossbars can directly switch variable size packets, but require large crosspoint buffers to do so, especially when jumbo frames are to be supported. When this is not feasible, segmentation and reassembly (SAR) must be used. We propose a novel SAR scheme for buffered crossbars that uses variable-size segments while merging multiple packets (or fragments thereof) into each segment. This scheme eliminates padding overhead, reduces header overhead, reduces crosspoint buffer size and is suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…We model variable size transfer units at the switch interfaces and the core, so in order to keep track of time we follow the discrete event simulation approach [15]. Information relative to the simulator can be found in [12].…”
Section: A Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We model variable size transfer units at the switch interfaces and the core, so in order to keep track of time we follow the discrete event simulation approach [15]. Information relative to the simulator can be found in [12].…”
Section: A Methodsmentioning
confidence: 99%
“…A subsequent observation was that buffered crossbars can directly switch variable-size packets [6] [11]. Doing so, without any segmentation, eliminates the need for speedup to cope with cell-padding overhead; in turn, the lack of speedup eliminates egress queueing, and the lack of segmentation eliminates reassembly buffers, thus reducing cost [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation results demonstrate that the proposed architecture outperforms unbuffered crossbar switches. A segmentation and reassembly (SAR) scheme was proposed in [9]. It uses variable size segments while merging multiple packets into each segment.…”
Section: Related Workmentioning
confidence: 99%
“…Jumbo frames and its impact on TCP packet processing is the subject of research in [4] and it is shown that jumbo frames can form a substantial component in data transfer. Performance under maximum-segment sizes is discussed in [5] and shown that segment size does affect performance. The impact of using jumbo frames in field-buses and multimedia applications to enhance performance is presented in [6].…”
Section: Introductionmentioning
confidence: 99%